2007
DOI: 10.1056/nejmoa062770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aircraft-Cabin Altitude on Passenger Discomfort

Abstract: Ascent from ground level to the conditions of 7000 to 8000 ft lowered oxygen saturation by approximately 4 percentage points. This level of hypoxemia was insufficient to affect the occurrence of acute mountain sickness but did contribute to the increased frequency of reports of discomfort in unacclimatized participants after 3 to 9 hours. (ClinicalTrials.gov number, NCT00326703 [ClinicalTrials.gov].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 13 publications
(2 reference statements)
5
94
0
6
Order By: Relevance
“…1,2 Term and preterm infants without BPD in our study had an important drop in SpO 2 during the preflight test (9% and 8%, respectively). Interestingly, we found that all neonates >39 weeks CGA and those without BPD passed the test.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1,2 Term and preterm infants without BPD in our study had an important drop in SpO 2 during the preflight test (9% and 8%, respectively). Interestingly, we found that all neonates >39 weeks CGA and those without BPD passed the test.…”
Section: Discussionmentioning
confidence: 94%
“…It is already well known that pulse oxygen saturation (SpO 2 ) declines significantly in healthy children and adults (∼4%, down to 94.4%) during commercial airline travel, but this is not considered pathologic. 1,2 Newborns are particularly susceptible to hypoxemic episodes in a hypoxic environment because of factors such as an increased tendency for ventilation-perfusion mismatch and a left shift of the oxygen dissociation curve due to fetal hemoglobin in the first months of life. 3 Premature infants have more apneic pauses and periodic breathing when they reach term than term infants, and apneic pauses may be triggered by chronic hypoxemia.…”
mentioning
confidence: 99%
“…Além disso, passeios e estadias em altitudes elevadas por períodos curtos ou prolongados a trabalho também são muito praticados 1,2 . A elevação da altitude faz com que a pressão barométrica em relação ao nível do mar diminua, resultando em uma redução da pressão parcial de oxigênio (O 2 ) para o organismo (sangue e tecidos corporais) 3 .…”
Section: Introductionunclassified
“…An average drop in O 2 saturation of 4% has been found in healthy passengers seated in air cabins at altitudes of 8000 feet. 105 Stable oxygenation can be achieved during air flight transport and mechanical ventilation. In studies from Iraq, 22 patients requiring mechanical ventilation were continuously monitored during transport from Balad to Germany, with an average flight time of 6-8 hours at altitudes of 37,000 feet.…”
Section: Mode Of Transportmentioning
confidence: 99%